Eating with Mrs Rundell - Batchelor , Ray (Petits Propos Culinaires, 2024)
Ray Batchelor works at the Science Museum in South Kensington. His exploration of Mrs Rundell’s recipes reminded us that we plan to reprint the very rare first edition of her book (1806), of which we have a copy. To the best of our knowledge this was the only edition for which she herself was fully responsible, since the publisher added material to later editions. But it may be that she herself provided the additions of the (’new’ and ’corrected’) edition of 1807. Any volunteers to do research on this obscure point? Meanwhile we have added a little editorial appendix at the end of Ray Batchelor’s article, relating the three recipes of his choice to the first edition.